Kajian Retorika Visual: Fotografi Potret Studio - Irwandi, G.R. Lono Lastoro Simatupang,And Soeprapto Soedjono (Rekam: Jurnal Fotografi, Televisi, Animasi)
A study about photography art work in Indonesia is rarely done. Thefact is that the potrait photography discourse in Indonesia is pointed to thecreative process of the creation of the art work and tends to place the potrait photography is more to be a mass product along with its economical value. To fulfill that emptiness, it needs a study which can be used as an explanation on how the portrait photography is evolve among society, one is relate to the human effort who express her/himself through a studio portrait photography.One of the efforts that can be done is inquiring the dimension ofcommunication in portrait photography which is using visual retoric theories. The outline of visual retoric theory has been oftenly used to analyze visual media in general, however it seems seldom chosen to analyze photography art work. Through this writing would be shown the example of theories which could be The theory outline is hoped to be able to give an illustration about many kinds of portrait photography shape and it is hoped to explain the main goal and the pattern of message deliverence photographically and to know how the society figure out the value of portrait photography for her/himself.